ANALISIS BIAYA PRODUKSI DAN BREAK EVEN POINT (TITIK IMPAS) SEBAGAI ALAT PERENCANAAN LABA PADA INDUSTRI TAHU DESA KARANG ANYAR KECAMATAN BERINGIN KABUPATEN DELI SERDANG - Fauzi, Indra; Hidayat, Toni; Antoro, Budi; Masitah, Tina Herianty; Maharani, Fitria (UNIVERSITAS DHARMAWANGSA, 2025)
This research seeks to examine Production Costs and the Break-Even Point as strategic tools for profit planning in Mrs. Paya’s tofu enterprise, located in Karang Anyar Village, Beringin Subdistrict, Deli Serdang Regency, North Sumatra. The study employs a descriptive quantitative approach. The sampling method utilized in this research is the saturated sampling technique.The results showed that annual production costs fluctuated, with total production costs of IDR 653,381,000 in 2021, IDR 717,850,000 in 2022, and IDR 654,628,000 in 2023. The break-even point for 2021 is 130,676 units, for 2022 is 143,570 units, and for 2023 is 130,926 units. The profit earned for each year is IDR 653,379,000 for 2021, IDR 717,850,000 for 2022, and IDR 654,632,000 for 2023.